Social Problems in Major League Baseball: Revisiting and Expanding Talamini’s Analysis Twenty Years Later - Mark Vermillion; G. Clayton Stoldt; Jordan Bass (Journal of Applied Sports Management, 2009)
The purpose of this research was to review, revisit, and expand Talamini’s social problems within Major League Baseball (MLB). Talamini’s categories, which include gambling, player/managerial violence, spectator violence, cheating, crime, and greed are reviewed and applied to social problems in MLB since the original publication in 1987. In order to better understand social problems and deviant behavior within MLB, the original categories are related to specific deviance theories to better understand causation of deviance. Theories are then organized by Shoemaker’s proposed integrated model, which organizes causes of deviance on the structural, social-psychological, and psychological levels. Relating Talamini’s social problems categories to sociology of deviance theories, and then organized by Shoemaker’s proposed integrated model aids in better explaining MLB deviance. Recommendations are made to sport management practitioners, students, and scholars regarding how to ameliorate the aforementioned social problems.
Keywords: baseball; Major League Baseball; deviance; social problems; sport sociology